2016
DOI: 10.17576/pengurusan-2016-47-06
|View full text |Cite
|
Sign up to set email alerts
|

Impak Kecekapan Kos terhadap Risiko Kecairan dalam Institusi Perbankan di Malaysia

Abstract: ABSTRAK Kajian ini menganalisis hubungan kecekapan bank dengan risiko kecairan ke atas 16 bank Islam dan 27 bank konvensional di Malaysia bagi tempoh 1994Malaysia bagi tempoh -2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
10
1
1
Order By: Relevance
“…This paper differs from Altunbas et al (2007) and Khalib et al (2016) studies in several aspects. First, they focused only on conventional European banks from 1992 to 2000 (Altunbas et al 2007) and banks in Malaysia (Khalib et al 2016), we focus on the difference between Islamic banks and conventional banks in selected 16 OIC countries from 1999 to 2013. This is important as the role of institutional factors do expose Islamic banks into different levels of efficiency that could have resultant impact on their liquidity risk differently from their conventional counterparts.…”
Section: Introductioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This paper differs from Altunbas et al (2007) and Khalib et al (2016) studies in several aspects. First, they focused only on conventional European banks from 1992 to 2000 (Altunbas et al 2007) and banks in Malaysia (Khalib et al 2016), we focus on the difference between Islamic banks and conventional banks in selected 16 OIC countries from 1999 to 2013. This is important as the role of institutional factors do expose Islamic banks into different levels of efficiency that could have resultant impact on their liquidity risk differently from their conventional counterparts.…”
Section: Introductioncontrasting
confidence: 56%
“…Altunbas et al (2007) documented positive efficiency-liquidity risk relationship in both directions. While Khalib et al (2016) found efficiency has no significantly related with liquidity risk in short term but negatively related in long term. This paper differs from Altunbas et al (2007) and Khalib et al (2016) studies in several aspects.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Research in banks merger and acquisitions in Malaysia mostly concentrated on the efficiency of banks (Ab-Hamid et al 2017). The majority of researchers use nonparametric frontier analysis such as Data Envelopment Analysis (DEA) and Malmquist productivity index (MPI) to assess the efficiency of the merged banks (Abd-Kadir et al 2010;Khalib et al 2016;Mat-Nor et al 2006;Mohd Said et al 2008;Sufian & Habibullah 2013). From their findings, most of the authors found significant efficiency gains after the merger except for Mohd Said et al (2008).…”
Section: Literature Reviewmentioning
confidence: 99%